2021
DOI: 10.3389/fpsyg.2021.699750
|View full text |Cite
|
Sign up to set email alerts
|

Inclusiveness of the Concept of Mental Disorder and Differences in Help-Seeking Between Asian and White Americans

Abstract: Ethnic and racial group differences in help-seeking are a barrier to the effective and equitable delivery of mental health services. Asian American populations demonstrate relatively low levels of help-seeking. Explanations for this effect typically point to elevated levels of stigma in these populations. An alternative explanation is that low help-seeking might also reflect holding a relatively circumscribed concept of mental disorder. Individuals and groups with less inclusive concepts of disorder may be les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 73 publications
1
17
1
Order By: Relevance
“…Having or reporting a mental health issue is a culturally stigmatizing issue in many AA communities, and these issues are often felt to be a sign of personal weakness which may bring dishonor or “shame” to a family’s reputation (Augsberger et al, 2015; Choi et al, 2016; Kim, 2011; Kim et al, 2015; Sue et al, 2012; Tse & Haslam, 2021; Woo, 2017; Yang et al, 2020). As such, the increase in reported rates of mental health distress might be due to a greater willingness to report psychological distress, or a true increase in psychological distress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having or reporting a mental health issue is a culturally stigmatizing issue in many AA communities, and these issues are often felt to be a sign of personal weakness which may bring dishonor or “shame” to a family’s reputation (Augsberger et al, 2015; Choi et al, 2016; Kim, 2011; Kim et al, 2015; Sue et al, 2012; Tse & Haslam, 2021; Woo, 2017; Yang et al, 2020). As such, the increase in reported rates of mental health distress might be due to a greater willingness to report psychological distress, or a true increase in psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…They also have the “best” self-reported personal health status, with over 40% claiming to be “excellent.” Despite this, however, South Asian women have some of the highest suicide ideation and depression rates in the United States (Augsberger et al, 2015; Choi et al, 2016; Karasz et al, 2019; Sue et al, 2012). Asian Indians have the largest immigrant population out of all groups studied, with over 90% being foreign born, indicating this group to be susceptible to acculturation issues—most prominently, stigma against acknowledgment of mental health issues (Augsberger et al, 2015; Choi et al, 2016; Derr, 2015; Sue et al, 2012; Tsai-Chae & Nagata, 2008; Tse & Haslam, 2021). With a large immigrant population, Asian Indians may experience difficulty in assimilating to the new host culture, which can include the concealment of mental health issues, utilization of alternative resources, and beliefs that American mental health professionals may not understand their problems and experiences (Augsberger et al, 2015; Choi et al, 2016; Derr, 2015; Sue et al, 2012; Tsai-Chae & Nagata, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Tse and Haslam (2021) indicates that the breadth of these lay concepts has implications for mental health help-seeking. They showed that people who held more inclusive concepts of mental illness, categorizing a wider variety of experiences and actions as disordered, had more favorable help-seeking attitudes.…”
Section: Research On Concept Creepmentioning
confidence: 99%
“…The work of Tse and Haslam (2021) is a case in point, providing a detailed account of how concept creep might have specific benefits. They demonstrated that holding favorable attitudes to mental health help-seeking is associated with more inclusive concepts of mental disorder, and that cultural differences in the inclusiveness of these concepts are associated with differences in help-seeking.…”
Section: Implications Of Concept Creep For Psychiatrizationmentioning
confidence: 99%